Incidental Detection of Viral Conjunctivitis on 68Ga-DOTANOC PET/CT in a Patient Suspected With Von Hippel–Lindau Syndrome. (21st May 2022) - Mathur, Yamini; Krishnaraju, Venkata Subramanian; Singh, Harmandeep; Kumar, Rajender; Dutta, Pinaki
Abstract: Von Hippel–Lindau syndrome is an autosomal dominant disorder. It is associated with a spectrum of benign and malignant tumors, including pancreatic and adrenal neuroendocrine tumors, renal cell carcinoma, and hemangioblastomas of the central nervous system and retina. 68 Ga-DOTANOC PET/CT has shown somatostatin receptor expression in inflammatory conditions. In the present case, we report that 68 Ga-DOTANOC PET/CT demonstrates the tracer avidity in the bilateral swollen eyelids in a patient with clinical suspicion of Von Hippel–Lindau syndrome, which was confirmed as viral conjunctivitis on clinical examination.